PENERAPAN TEXT MINING UNTUK ASSINGMENT COMPLAINT HANDLING CUSTOMER TERHADAP DIVISI TERKAIT MENGGUNAKAN METODE DECISSION TREE ALGORITMA C4.5 (STUDI CASE : PT. XL AXIATA, TBK) - Dedi Dwi Saputra; Bryan Pratama; Yuma Akbar; Windu Gata (CKI ON SPOT, 2018)
ABSTRACTError assignment on customer complaints handling against a division causes customer complaints not to be processed optimally, this can lead to a negative war of mouth in a company. The purpose of this research is to make an implementation of handling customer complaints towards a division processed optimally by using text mining and the C4.5 algorithm. From the results of these research will be evaluated and validated with the ROC curve to determine the level of accuracy on the decision tree in making classification of complaint handling of the division. With this decision support system, it’s expected to facilitate and accelerate a complaint from the customer and maximize customer service performance in the company PT. XL Axiata, Tbk.Keywords: Customer; Complaint handling; Text mining; Decission tree; Algoritma C4.5;